2014
DOI: 10.7763/ijfcc.2014.v3.319
|View full text |Cite
|
Sign up to set email alerts
|

A P2P-MCU Approach to Multi-Party Video Conference with WebRTC

Abstract: Abstract-WebRTC enables web browsers with real-time communications capabilities via JavaScript APIs. But when the number of the participants increases, the bandwidth and CPU requirements have become a serious issue in a push based mesh network. In this paper, we propose a P2P-MCU approach for multi-party video conferencing that efficiently supports both ordinary smart mobile phones and PCs. In our approach, a MCU module is integrated into the browser to mix and transcode the video & audio streams in real time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The authors elaborated on the proposed method and how it offers high resolutions such as session recording and stream processing. Another study performed by Fai Ng et al [15] showed that the use of MCU was extremely expensive but it can be subscribed to some providers at the time of the conference. Also, the developers in [16] approved that MCU cannot support heterogeneous endpoints or when having a large number of participants.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors elaborated on the proposed method and how it offers high resolutions such as session recording and stream processing. Another study performed by Fai Ng et al [15] showed that the use of MCU was extremely expensive but it can be subscribed to some providers at the time of the conference. Also, the developers in [16] approved that MCU cannot support heterogeneous endpoints or when having a large number of participants.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…According to the aforementioned description and the literature, MCU in usual situations presents failure quality of video conferencing, which eventually affects the whole performance of the conference [15]. Hence, this paper comes to overcome these issues and suggest an approach that guarantees to provide reliable and high-quality performance.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…5(c)]. Deployment of the central server can be as a standalone hardware component [38] or a cloud-based service [39]. We discuss the implementation and evaluation of different connection architectures in SEC.…”
Section: Connection Architecturesmentioning
confidence: 99%
“…The web browser, as an interactive platform for real-time communications, has seen a rapid rate of development and expansion in capabilities in support of online collaboration. In particular the WebRTC standard provides peer-topeer connectivity, media device capture and streaming over User Datagram Protocol (UDP), and binary data streaming over Stream Control Transmission Protocol (SCTP) [38,44]. UDP, an inherently unreliable 'best-effort' protocol, is commonly used in media streaming over the Internet owing to its low-latency delivery of data packets [45].…”
Section: Real-time Online Group Communicationmentioning
confidence: 99%